Chemical Feedback From Decreasing Carbon Monoxide Emissions. Issue 19 (4th October 2017) - Gaubert, B.; Worden, H. M.; Arellano, A. F. J.; Emmons, L. K.; Tilmes, S.; Barré, J.; Martinez Alonso, S.; Vitt, F.; Anderson, J. L.; Alkemade, F.; Houweling, S.; Edwards, D. P.
Abstract: Understanding changes in the burden and growth rate of atmospheric methane (CH4 ) has been the focus of several recent studies but still lacks scientific consensus. Here we investigate the role of decreasing anthropogenic carbon monoxide (CO) emissions since 2002 on hydroxyl radical (OH) sinks and tropospheric CH4 loss. We quantify this impact by contrasting two model simulations for 2002–2013: (1) a Measurement of the Pollution in the Troposphere (MOPITT) CO reanalysis and (2) a Control‐Run without CO assimilation. These simulations are performed with the Community Atmosphere Model with Chemistry of the Community Earth System Model fully coupled chemistry climate model with prescribed CH4 surface concentrations. The assimilation of MOPITT observations constrains the global CO burden, which significantly decreased over this period by 20%. We find that this decrease results to (a) increase in CO chemical production, (b) higher CH4 oxidation by OH, and (c) 8% shorter CH4 lifetime. We elucidate this coupling by a surrogate mechanism for CO‐OH‐CH4 that is quantified from the full chemistry simulations. Key Points: Decreases in tropospheric CO from 2002 to 2012 indicate an increase in CH4 chemical loss There is a positive trend in the chemical production of CO from CH4 in the tropics We infer a reduced growth rate in CH4 burden due to decreases in anthropogenic CO emissions